Approximations of the Colombia´s insertion in the multilateral trading system in 1995-2015 [Aproximaciones a la inserción de Colombia en el sistema multilateral de comercio en 1995-2015] (2016)
The discussion about protectionism and free trade remains at time, especially when the global economic crisis poses scenarios where governments and policy makers consider solutions which can be tilted any of these doctrines. In this sense, this article establish the main reasons that Colombia had to be inserted into the process of economic liberalization which still it is promoted by the multilateral trading system and which are also, in general, the benefits of taking this decision in its trade policy. Likewise the article aims to characterize during the past 20 years, from 1995-2015, the effects to implement protectionist policies in some industrial sectors in Colombia; also it seeks to analyze the behavior of the industrial sector in the country since its inception to the WTO and also identify the level of economic liberalization respect other countries, to finally establish some conclusions about the meaning of this process. © 2016, Universidad Nacional de Colombia. All rights reserved.